Future directions for Indonesian academic library education - Maesaroh, Imas; Genoni, Paul (Emerald, 2013)
Purpose – This paper aims to provide 13 recommendations relating to the future of Indonesian library education based on the results of an extensive research study. The objective of the research was to investigate the desired level of educational qualifications and continued professional development of Indonesian academic librarians.Design/methodology/approach – The research included surveys of Indonesian academic librarians and their managers, plus extensive interviewing of stakeholders. The recommendations have been developed on the basis of data gathered in this research.Findings – There is an immediate need to raise the standards of Indonesian library education in order to enhance skills required of the contemporary library workforce. The Indonesian Librarian Association has an important role to play in raising the quality of library education and the status of librarians.Practical implications – The recommendations have far-reaching implications for Indonesian library education. There are also implications for the wider Indonesia library profession, and for the professional associations, in particular the Indonesian Librarian Association.Originality/value – The recommendations are based on the first comprehensive analysis of the educational and continuing professional development needs of Indonesian academic librarians.